ANALISIS AKHLAK DALAM PANDANGAN HADIST - Harahap, Taufiqurrahman; br Ginting, Ernawati; Nawawi, Ahmad; Fajri, Khairul; Permana, Dimas Yudha (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to explore the views of the hadith of the Prophet Muhammad regarding morals and their implementation in everyday life, especially in the modern context. Considering the importance of morals in Islamic teachings, this research aims to provide an in-depth understanding of how the moral values taught in the hadith can be applied by Muslims in various life situations. The research method used is qualitative research through literature study with a content analysis process. Data was collected from various primary and secondary sources, then analyzed and categorized to detail themes according to the research questions. The next stage is the presentation of the core points which are able to summarize the research results descriptively related to morals from the perspective of hadith. The research results show that morals in the hadith view include good and commendable behavior, which is instilled in every Muslim through the teachings of the Prophet Muhammad. Hadiths that teach values such as honesty, patience, compassion and justice provide practical guidance for Muslims. However, in the context of modern life, the application of these morals faces complex challenges due to social change and globalization. Keywords: Akhlak; Hadith; Impelementation.